Respiratory symptoms after coalmine fire and pandemic: A longitudinal analysis of the Hazelwood Health Study adult cohort. - Tyler J Lane; Matthew Carroll; Brigitte M Borg; Tracy A McCaffrey; Catherine L Smith; Caroline X Gao; David Brown; Amanda Johnson; David Poland; Shantelle Allgood; Jillian Ikin; Michael J Abramson (PLOS Global Public Health)
The aim of this study was to determine whether the effects of extreme but discrete PM2.5 exposure from a coal mine fire on respiratory symptoms abated, persisted, or worsened over time, and whether they were exacerbated by COVID-19. We analysed longitudinal survey data from a cohort residing near a 2014 coalmine fire in regional Australia. A 2016/2017 survey included 4,056 participants, of whom 612 were followed-up in 2022. Items included respiratory symptoms, history of COVID-19, and time-location diaries from the mine fire period, which were combined with geospatial and temporal models of fire-related PM2.5. Longitudinal effects of fire-related PM2.5 were examined using a mixed-effects logistic regression model. Exacerbation due to COVID-19 was examined using a logistic regression model. PM2.5 exposure was associated with chronic cough and possibly current wheeze, chest tightness, and current nasal symptoms 2-3 years post-fire, and chronic cough and current wheeze 8.5-9 years post-fire. Further, the association between PM2.5 and chronic cough and possibly current wheeze appeared to increase between the survey periods. While there were no detectable interactions between PM2.5 and COVID-19, PM2.5 exposure was associated with additional respiratory symptoms among participants who reported a history of COVID-19. In summary, medium-duration exposure to extreme levels of fire-related PM2.5 may have increased the long-term risk of chronic cough and current wheeze. While the COVID-19 pandemic started several years after the mine fire, contracting this illness may have exacerbated the effect of fire-related PM2.5 through development of additional respiratory symptoms.